In Vitro analysis of the effect of mono-(2-ethylhexyl) phthalate (MEHP) exposure on macrophage inflammatory responses in relationship to Leydig cell steroid production - Adla, Akhil; Lunney, Allison; Zirkin, Barry; Traore, Kassim (Frontiers in Toxicology, 2025)
Macrophages, essential components of the innate immune system, are considered to be involved in the regulation of Leydig cell steroidogenesis, though by mechanisms that remain uncertain. Mono-(2-ethylhexyl) phthalate (MEHP), the active metabolite of di-(2-ethylhexyl) phthalate (DEHP), has been shown to affect testosterone production directly via its effects on Leydig cells, but also has been implicated in immune system modulation. These observations raise the possibility that MEHP might affect male steroidogenesis both by its direct effects on Leydig cells and perhaps also indirectly through its effects on macrophages. As yet, however, MEHP effects on macrophages and the potential relationship between macrophage response and Leydig cell steroidogenic function are poorly understood. Using in vitro methodology, we investigated the effects of MEHP on macrophage function and of downstream effects of changes in macrophage function on Leydig cell steroidogenesis. Mouse macrophage RAW 264.7 cells were cultured with MEHP (0–300 µM) for 24 h. Significant dose-dependent changes were seen in these cells in response to MEHP exposure, including increased cell size and granularity, increased mitochondrial content and membrane potential, decreased ATP production and oxygen consumption, and elevated intracellular and mitochondrial-derived oxidative stress. These changes suggested a pro-inflammatory response of the RAW 264.7 cells to MEHP. MEHP exposure activated the p38 MAPK pathway linking oxidative stress to inflammatory signaling and induced a dose-dependent increase in TNF-α secretion. In vitro exposure of MA-10 Leydig cells to TNF-α was found to inhibit steroid (progesterone) production by these cells. The observations, taken together, that TNF-α was secreted by MEHP-activated macrophages and that exposure to TNF-α can inhibit LH-stimulated steroid (progesterone) production by MA-10 Leydig cells suggest the possibility of the involvement of an immune-mediated mechanism resulting from MEHP exposure on impaired Leydig cell steroid production.